Трансляция природных мРНК. I. Общий кинетический анализ процесса трансляции мРНК одного вида - Потапов, А.П.; Ельская, А.В. (Биополимеры и клетка, 1986)
Дан общий теоретический анализ стационарной кинетики трансляции природной мРНК. Получены уравнения зависимости скорости образования белкового продукта от концентрации рибосом, кинетических характеристик считывания отдельных кодонов матрицы. С учетом выявленных особенностей трансляции мРНК в составе полирибосомных комплексов сделан вывод о важности полирибосомной организации аппарата трансляции для создания высокой чувствительности систем белкового синтеза к регуляторным воздействиям. Зроблено загальний теоретичний аналіз стаціонарної кінетики трансляції природної мРНК. Отримано рівняння залежності швидкості утворення білкового продукту від концентрації рибосом, кінетичних характеристик зчитування окремих кодонів матриці. З урахуванням виявлених особливостей трансляції мРНК у складі полірибосомних комплексів зроблено висновок про важливість полірибосомної організації апарату трансляції для створення високої чутливості систем білкового синтезу до регуляторних впливів. Steady-state kinetics of natural mRNA translation is theoretically analyzed. Equations are obtained for describing dependence of the total rate of cistron translation on the specific rates of each codon reading. The limited capacity of mRNA for ribosomes is shown to limit the increase of the total translation rate. Vmax depends on the sequence of mRNA codons and specific rates of codon reading. For the polyribosomal system, whose total translation rate is close to Vmax, the dependence of the total rate on specific rates of codon reading may be significantly stronger than that for the monoribosomal system. Thus, polysomal organization of the translation apparatus is suggested to be of importance for providing high susceptibility of the translation system to the regulatory factors.